The Role of Peer Counselors in Breast Self-Examination in Increasing Female Teenagers’ Self-Awareness - Retno Apriliyanti; Sindy Septi Verawati; Susi Nurhayati (JENDELA NURSING JOURNAL, 2022)
Background: breast self-examination is a systematic breast self-examination by a woman for the purpose of detecting abnormalities in the breast which is carried out every month. To increase adolescent self-awareness, health education is needed, namely peer counseling which helps peer counselors. In addition to peer activities, the provision of leaflets about breast self-examination also helps counseling in providing informationPurpose: this study was to know the effectivity of peer counselor counseling and leaflets about breast self-examination towards students’ self-awareness.Methods: this study uses a Quasy Experiment approach a pre-test and post-test without control group design. The research sample was 40 respondents. Collecting data used a questionnaire that has been tested by expert on Maternity Nursing. Data analysis used the paired sample t-test in the paired group while the independent sample t-test in the unpaired groupResults: the results that self-awareness before the group was given peer counselor treatment had an average of 67.10 and given after peer counselors about breast self-examination had an average of 100.50 while in the control group self-awareness before being given leaflets an average of 68.50 and after being given leaflets an average of 73.35. There are differences in peer counselors regarding breast self-examination on self-awareness of students with p value = 0.000.Conclusion: follow-up process is still needed to increase self-awareness in carrying out breast self-examination and coordination from the school.